Self Efficacy dan Perilaku Sehat dalam Modifikasi Gaya Hidup Penderita Hipertensi - Fatmawati, Baiq Ruli; Suprayitna, Marthilda; Istianah, Istianah (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2021)
Hypertension is one of chronic diseases and the main concern because of its high morbidity and mortality. Confidence in care and lifestyle changes called cell efficacy is needed. Self-efficacy, a widely used psychosocial concept, is associated with the ability to manage chronic disease. The purposes of this study were to analiyze the correlation between self-efficacy with lifestyle on hypertension patients. The data obtained were analyzed by correlational analytic with a cross-sectional approach. The sample of this study was recruited with total sampling as much as 30 people. The data were analyzed by Spearman correlation with significance α<0.05. The study showed that self-efficacy of patients with hypertension was majorly high(73,3%), and lifestyle was a majorly healthy lifestyle (83,3%). There was a significant correlation between self-efficacy with lifestyle on hypertension patients (r=0.893; p<0.05). Nurses can increase self-efficacy of hypertension patients by providing support and motivation to improve a healthy lifestyle to prevent further complications